Synergistic effects of plasma-activated water and potassium chloride on the structure, function, and digestibility of low-sodium chicken myofibrillar protein - Deng, Lanting; Li, Junqi; Ismail-Fitry, Mohammad Rashedi; Sun, Yangying; Xia, Qiang; Zhou, Changyu; Pan, Daodong; Cao, Jinxuan; Du, Lihui (Elsevier, 2025)
Excessive sodium intake is a major health concern, however, reducing salt in meat products often compromises the functional quality of myofibrillar protein (MP). This study investigated the synergistic effects of cold plasma-activated water (PAW) and potassium chloride (KCl) on the structure, functionality, and digestibility of low-sodium (0.3 M NaCl) chicken MP. While 0.3 M NaCl alone significantly impaired MP functionality, an 8-min PAW treatment combined with 0.1 M KCl produced a significant synergistic effect. This combined treatment remarkably improved the rheological properties, increasing the storage modulus by 10.42% and gel strength by 63.32% compared to the 0.3 M NaCl control. These functional enhancements were attributed to structural modifications, including an increase in β-sheet content, a reduction in surface roughness, and the formation of a denser, more uniform gel network. Furthermore, the combined treatment significantly enhanced in vitro digestibility and promoted the release of bioactive peptides. LC-MS/MS analysis identified eight novel peptide sequences with potential bioactivity. In conclusion, the combination of PAW and KCl provides an effective strategy to mitigate the negative effects of sodium reduction, improving the textural quality of low-sodium chicken MP while simultaneously generating health-promoting bioactive peptides. This approach offers a promising solution for developing healthier, high-quality meat products with both desirable texture and added health benefits.